Elsevier reference collection in chemistry, molecular sciences and chemical engineering (Elsevier, 2013)
This online Reference Collection forms the definitive source for those entering, researching or teaching in any of the many disciplines making up this interdisciplinary area of study. This resource is designed to serve as an in depth and comprehensive compendium of Chemistry, Molecular Sciences & Engineering